Bibliometric Analysis Of Sustainable And Green Consumption Research From 1974 To 2019 - et. al., Nornajihah Nadia Hasbullah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The past decade witnessed the resurgence of sustainable consumption due to the strong support offered by companies, consumers, institutions, and society. Nevertheless, examination of sustainable consumption via bibliometric and network analyses is absent from the vast literature. In order to bridge this gap, a bibliometric analysis was performed on all publications related to sustainable consumption in the Scopus database for the period of 1974-2019. Upon analyzing 2352 articles, several parameters were determined, namely the trends in publications, the most popular journals, the productive countries of the most important countries, most of the studies cited and the list of keywords for further description (psychosocial factors).From the selected 160 journals, articles were most-frequently published in Sustainability Switzerland, while the Journal of Consumer Marketing ranked first for total citation. The emergence of sustainable consumption topic was spread across 120 countries and 159 academic institutions. This present study discovered that the United States dominated publication production, whereas Universität Göttingen in Germany was the most productive institution. Upon further systematic analysis using VOS viewer, 5333 keywords were listed. The top four clusters of psychosocial determinants were discussed in light of social norm, attitude, environmental concern, and perceived value. Building on the outcomes retrieved from this analysis, researchers may better plan their studies and contribute better insights of their empirical investigations.